On left fq-derivations of B-algebras - Egytia Yattaqi; Sri Gemawati; Ihda Hasbiyati (Science, Technology, and Communication Journal, 2021)
In this paper, we introduce the notion of left fq-derivation of B-algebra and investigate some related properties. Among them are properties of left fq-derivation  of B-algebra  and given properties of . Then, we discuss the properties of the regularleft fq-derivation on B-algebras and composition properties of fq-derivation on particular B-algebra, namely on BM-algebra.